The dog who cried "Woof!" - Barkly, Bob.; Kurtz, John (New York : Scholastic, 2001)
Because Cleo had fooled them twice before, Clifford and T- Bone ignore her cries for help.
"From the television script, 'The dog who cried "Woof!"' by Anne-Marie Perrotta & Tean Schultz; based on the Scholastic book series 'Clifford the big red dog' by Norman Bridwell.
100
Accelerated Reader AR
Keywords: Dogs -- Fiction; Skunks -- Fiction